A Design of Experiments Approach to the Radical-Induced Oxidation of Dimeric C4-C8 Linked B-Type Procyanidins - Annik Fischer; Recep Gök; Tuba Esatbeyoglu (Molecules)
This study systematically investigated the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical induced oxidation of all dimeric C4-C8 linked B-type procyanidins (PCs) B1–B4 to maximise the formation of the oxidation products using a Design of Experiments (DoE) approach. The C4β-C8 linked B1 and B2 formed the A1 (1) and A2 (2) (m/z 575 [M-H]−) with an ether bridge between C2u-O-C7t as expected. Interestingly, the oxidation of the C4α-C8 linked dimers B3 and B4 yielded for each two main oxidation products with m/z 575 [M-H]−. One of them required only a short reaction time (10.0 min, 25.0 °C for B3 (3) and B4 (5)), whereas the other was maximally formed at a longer time and higher temperature (314 min and 75.0 °C for B3 (5); 360 min, 53.7 °C for B4 (6)). The formation rates were optimised to 47.4 ± 1.14% (A1; 1), 27.5 ± 0.76% (A2; 2), 48.6 ± 4.01% (3), 32.0 ± 1.14% (4), 45.0 ± 5.14% (5) and 60.2 ± 3.68% (6).